2017
DOI: 10.1094/cchem-04-16-0119-fi
|View full text |Cite
|
Sign up to set email alerts
|

Development of Low Glycemic Index (GI) Foods by Incorporating Pulse Ingredients into Cereal‐Based Products: Use of In Vitro Screening and In Vivo Methodologies

Abstract: Cereal Chem. 94(1):110-116Pulse ingredients (pea and lentil flour, pea protein, and pea fiber) were incorporated into 94 different food products. Products included pastas, breads, crackers, extruded snacks, cookies, cereal bars, and muffins. Products were screened for estimated glycemic index using an in vitro method. Based on the screening results, five products (pasta, bread, cracker, granola bar, and cookie) were selected for in vivo glycemic index (GI) testing. For each control (containing 100% wheat flour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 34 publications
3
37
0
3
Order By: Relevance
“…Indeed, previous studies also revealed that incorporation of high fibre ingredient in bakery production could be a promising strategy to significantly decrease the GI in vivo. For example, it was reported that substituting the wheat flour with dietary fiber-rich pulse ingredients could reduce the GI value of cereal-based products in vivo (Fujiwara, Hall, and Jenkins 2016). Besides, Ferrer-Mairal also demonstrated that a reduction of GI value in the in vitro and in vivo was achieved with the partial substitution of wheat flour by dietary in muffin and breads (Ferrer-Mairal, Peñalva-Lapuente, et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies also revealed that incorporation of high fibre ingredient in bakery production could be a promising strategy to significantly decrease the GI in vivo. For example, it was reported that substituting the wheat flour with dietary fiber-rich pulse ingredients could reduce the GI value of cereal-based products in vivo (Fujiwara, Hall, and Jenkins 2016). Besides, Ferrer-Mairal also demonstrated that a reduction of GI value in the in vitro and in vivo was achieved with the partial substitution of wheat flour by dietary in muffin and breads (Ferrer-Mairal, Peñalva-Lapuente, et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, YP and YP-U were selected as study foods for measurements of GI and the post-consumption insulin responses in this study. In previous studies, the GI of noodles made with wheat and pea (70% and 30%, respectively) or wheat and lentil (50% each) were reported as 93 and 55, respectively, with a reference food of white bread [24,25]. These reports attempted to verify that the GI was reduced by mixing the main ingredient with legume; however, the GI was not significantly lower than the wheat-only control food [24,25].…”
Section: Blood Glucose/insulin Response From Noodles Made From Legumesmentioning
confidence: 99%
“…Cereals and pulses are frequently used in their native flour form as these are relatively inexpensive compared to purified products such as starches or protein isolates and concentrates, or chemically/physically modified flours. There is growing interest in the incorporation of legume flours into traditional cereal‐based foods such as bread, pasta, cookies, and extruded snack products (Fujiwara, Hall, & Jenkins, ; Sozer, Holopainen‐Mantila, & Poutanen, ) as well as an increase in new pulse products. This is supported by the introduction of over 1,000 new pulse containing products in the United States and Canada, combined, in 2016 which is attributed to the consumer pursuit for healthy natural foods as well as the rise in demand for gluten‐free foods (AAFC, ).…”
Section: Introductionmentioning
confidence: 99%